On the Pedagogy of “Boomerangs”: Exposing Occupation Through Co-Implication - Klinker, Mary Jo; Morrison, Heidi (Radical Teacher, 2020)
This article explores the pedagogical takeaways of a faculty led study-tour with U.S. university students in the Occupied Palestinian Territories. It offers examples of how to teach students first-hand about settler colonialism, neoliberalism, securitization, and racialization. We examine how theories of co-implication and bearing witness can encourage students to take part in transnational solidarity work.